2013
DOI: 10.17323/1814-9545-2012-4-109-185
|View full text |Cite
|
Sign up to set email alerts
|

Океаны Инноваций. Атлантический Океан, Тихий Океан, Мировое Лидерство И Будущее Образования (Пер. С Англ. Н. Микшиной)

Abstract: Барбер Майкл (Michael Barber) — профессор, главный советник по вопросам образования компании Pearson (Великобритания). Эл. адрес: krdonnelly @pearson.com Адрес: Institute for Public Policy Research, 4th Floor, 14 Buckingham Street, London WC2N 6DF, UK.Доннелли Кейтлин (Katelyn Donnelly) — исполнительный директор в аппарате главного советника по вопросам образования компании Pearson (Лондон). Эл. адрес: krdonnelly @pearson.com Адрес: Institute for Public Policy Research, 4th Floor, 14 Buckingham Street, London … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Education needs to change in order to meet the challenges of the transformation brought about by technology. Innovation is thus a necessity for bettering education for the future (Barber, Donnelly, & Rizvi, 2012;Goldin & Katz, 2008;Wagner, 2008Wagner, , 2012Zhao, 2012).…”
Section: Stifling Innovation In Educationmentioning
confidence: 99%
“…Education needs to change in order to meet the challenges of the transformation brought about by technology. Innovation is thus a necessity for bettering education for the future (Barber, Donnelly, & Rizvi, 2012;Goldin & Katz, 2008;Wagner, 2008Wagner, , 2012Zhao, 2012).…”
Section: Stifling Innovation In Educationmentioning
confidence: 99%
“…The researchers of the world educational systems Barber, Donnelly, and Rizvi (2012) undertook an intergenerational, intercivilizational, intercontinental synthesis of system-based innovations in the education of mankind in the last millennium and revealed that the 300-year superiority of the Atlantic was achieved by the colonial economy, that is external resources, and the culture of law, and the growing power of the Pacific countries comes from the nature of Asian society, which survived the colonial period through the culture of responsibility, which is their core feature. The authors of this study developed a model of a Cheung and Mok (2018) identified factors of teacher's creative ability, among which the cognitive ability of a creative personality was noted as the strongest predictor of creative pedagogical activity that may reflect the cultural characteristics of indigenous peoples.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…(Reynolds and Farrell 1996), derived from that study, which specifically promoted the importance of a didactic whole-class teaching pedagogy. More recently, Hong Kong's education system was referenced in consultancy reports by Barber, Donnelly and Rizvi (2012) and the Grattan Institute, the latter of which argued that 'Hong Kong provides a leading example of successful education strategy and implementation' (Jensen et al 2012, 23). A Government report (Ruddock and Sainsbury 2008), which compared England's mathematics, science, and literacy curricula with that of high performers in PISA, highlighted Hong Kong, along with Singapore and South Korea.…”
Section: Hong Kong As Fairytalementioning
confidence: 99%